2015
DOI: 10.1186/s12864-015-1316-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome gene expression profiling revealed genes and pathways potentially involved in regulating interactions of soybean with cyst nematode (Heterodera glycines Ichinohe)

Abstract: BackgroundSoybean cyst nematode (SCN, Heterodera glycines Ichinohe) is the most devastating pathogen of soybean. Many gene expression profiling studies have been conducted to investigate the responses of soybean to the infection by this pathogen using primarily the first-generation soybean genome array that covered approximately 37,500 soybean transcripts. However, no study has been reported yet using the second-generation Affymetrix soybean whole-genome transcript array (Soybean WT array) that represents appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 72 publications
4
59
0
Order By: Relevance
“…The initial feeding cell is expanded through dissolution of the surrounding cell walls to form a multinucleated structure, referred to as a syncytium (Jones, 1981;Jones and Northcote, 1972). Gene expression profiling studies performed on whole roots and microdissected syncytia have revealed extensive alterations in host gene expression in response to cyst nematode infection (Hermsmeier et al, 1998;Hofmann et al, 2010;Ithal et al, 2007;Puthoff et al, 2003;Szakasits et al, 2009;Wan et al, 2015). The secretion of effector proteins, defined by their ability to modify host cell structure and function, is key to the breakdown of plant tissue for migration and the suppression of plant defences Hogenhout et al, 2009;Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The initial feeding cell is expanded through dissolution of the surrounding cell walls to form a multinucleated structure, referred to as a syncytium (Jones, 1981;Jones and Northcote, 1972). Gene expression profiling studies performed on whole roots and microdissected syncytia have revealed extensive alterations in host gene expression in response to cyst nematode infection (Hermsmeier et al, 1998;Hofmann et al, 2010;Ithal et al, 2007;Puthoff et al, 2003;Szakasits et al, 2009;Wan et al, 2015). The secretion of effector proteins, defined by their ability to modify host cell structure and function, is key to the breakdown of plant tissue for migration and the suppression of plant defences Hogenhout et al, 2009;Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Diferential genetic expression proiles of many speciic genes involved in plant immune responses has been shown in resistant and susceptible plants challenged by root-knot nematodes [48,95]. The identiication of novel defenserelated transcripts and the elucidation of pathways involved in plant immune responses to nematodes have been recorded for important economic crops including coton [96], rice [97], and soybean [98]. Transcriptome proiling of resistant and susceptible tobacco varieties infected with root-knot nematodes has shown diferential expression paterns among genes involved in cell wall modiication, auxin production and oxidative stress [99].…”
Section: Mi-12 (Referred To Asmentioning
confidence: 99%
“…To investigate whether Pep seed treatments limit nematode infestation through transcriptional reprogramming of the roots, we examined the expression of several defence genes previously implicated in resistance to SCN or RKN. Genes encoding a putative respiratory burst oxidase protein (RBOHD) and a nucleotidebinding site leucine-rich repeat-type disease resistance protein (NBS-LRR) have been reported previously to be up-regulated by SCN infestation on resistant, but not susceptible, plants (Wan et al, 2015). In addition, a gene encoding a putative pectin methylesterase inhibitor (PMEI, Glyma10g02150) was identified as a candidate gene for RKN resistance through quantitative trait locus (QTL) mapping (Xu et al, 2013).…”
Section: Gmpeps Induce Defence Genes Regulating Soybean Resistance Inmentioning
confidence: 99%
“…Previous studies have shown that PTI against RKNs in Arabidopsis is compromised in mutants with impairments in BAK1, BIK1 or NADPH oxidase genes (RBOHD/F) (Teixeira et al, 2016). Comparison of transcript profiles induced by SCN in resistant versus susceptible soybean cultivars also indicates that BIK1 and RBOHD induction correlate with cyst nematode resistance (Matsye et al, 2011;Wan et al, 2015). Given that Peps induce defence responses that are also associated with PTI or ETI against nematodes, Peps could potentially be utilized to induce nematode resistance in susceptible genotypes.…”
Section: Introductionmentioning
confidence: 99%